The Reality of the Qatari Family and the Challenges Faced An Inter-generational Qualitative Study - Al-Otaibi, Afrah Farhan; Al-Hajry, Noura Hamad; Al-Sallabi, Sarah Ali; Malkawi, Asmaa (Journal of Humanities & Social Sciences, 2023)
The present study aimed to investigate the reality of the Qatari family experiencing social changes, especially the change in its structure and size in terms of the reduced presence of the extended family and its replacement with the nuclear family. The study asked various questions to explore the meaning of the family among different generations in Qatari society, from grandchildren to parents and grandparents. Furthermore, the positive and negative features of the Qatari family were listed from the perspective of different generations. The study also aimed to know the role of social, governmental, or international institutions that contributed to shaping the concepts of the family. Finally, the study sought to identify the challenges faced by the Qatari family from the perspective of the study sample. The study adopted a qualitative approach by using focus groups for grandchildren and parents while conducting in-depth interviews with male and female grandparents. It concluded that the generations of grandchildren and grandparents had similar views on the concepts of the family and on the positive and negative features of the Qatari family. Both generations preferred the extended family, unlike the parent generation, which did not show the same interest in reducing the presence of the extended family. From the perspective of grandchildren and grandparents, the extended family was a positive feature of the Qatari family, while the excessive financial cost was a negative one. It includes the costs associated with marriage in Qatari society, which poses a challenge for the male grandchildren. Moreover, the Qatari family has been facing the challenge of using modern technology, which affects parents in raising their children. The use of technology has also affected face to face communication, especially between grandparents and other generations.